Thermodynamic stability and formation kinetics of CHClF2 hydrates in the presence of NiCl2. (20th July 2019) - Woo, Yesol; Jeong, Jae Hak; Lee, Jong-Won; Park, Jeasung; Cha, Minjun; Kim, Dongseon; Yoo, Kyoungkeun; Yoon, Ji-Ho
Highlights: Hydrate-based desalination is developed to separate metal ions from wastewater. Metal ions cannot be trapped in the clathrate hydrate framework. Formation kinetics of clathrate hydrates depends on the concentration of metal ions. Abstract: A hydrate-based technology is suggested for the desalination of industrial effluents, especially electroplating effluents including NiCl2 . To decrease the required energy for operating a hydrate-based desalination (HBD) process, chlorodifluoromethane (CHClF2 ) was used as a guest for hydrate formation at relatively mild conditions. The phase equilibria of CHClF2 hydrates formed in aqueous NiCl2 solutions were investigated to identify the effect of NiCl2 on the thermodynamic stability of CHClF2 hydrates. The dissociation phase boundary of CHClF2 hydrates in the presence of NiCl2 was shifted to higher pressures and lower temperatures as the salinity of aqueous solutions increased. To confirm the feasibility of NiCl2 separation from wastewaters via the HBD process, X-ray diffraction and Raman spectroscopic measurements were performed. The results showed that the Ni 2+ and Cl − ions did not participate in the hydrate framework, which revealed that the HBD process could be used to remove NiCl2 from effluents. The formation kinetics of CHClF2 hydrates were analyzed by a new kinetic model adopting transient time-dependent apparent rate constants, which significantly depends on the sub-cooling temperature and the concentration of NiCl2 in the aqueous solutions. Thermodynamic approximations regarding the Ni 2+ and Cl − ion exclusion from the clathrate framework and the full occupancy of CHClF2 molecules in the large cages of structure I clathrate hydrate were confirmed by comparing the calculated Ni 2+ concentrations in the liquid phase in equilibrium with CHClF2 clathrate hydrates with the experimental measurements. These results provide good information for separating metal ions from wastewater streams by HBD processes.